Methane production catalyst as well as preparation method and application thereof

The catalyst precursor of the layered polymetallic hydroxide structure is prepared by structural topological transformation and reduction treatment, which solves the problem of low activity and selectivity of existing nickel-based catalysts under low temperature conditions, and achieves a catalytic effect of high activity, selectivity and stability.

CN119638542APending Publication Date: 2025-03-18CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411881971.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing nickel-based catalysts exhibit low activity and selectivity under low temperature conditions, and have poor stability, which is prone to sintering and depositing carbon at high temperatures, resulting in a degradation of performance.

Method used

A catalyst precursor with a layered polymetal hydroxide structure is used to prepare a hydrogenation catalyst through structural topological transformation and reduction treatment. The catalyst has a layered structure of Ni, M and Al. M includes elements such as Ce and Zr. The specific surface area and surface interface structure of the catalyst are adjusted by doping different M to improve catalytic activity.

Benefits of technology

The activity of carbon dioxide and the selectivity of methane are significantly improved under low temperature conditions, and the catalyst has high stability, avoiding the inactivation problem of sintered carbon deposits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention provides an application of a hydrogenation catalyst in CO / CO2 hydrogenation methane preparation. The hydrogenation catalyst is obtained by structural topological transformation and reduction of a catalyst precursor; the catalyst precursor has a layered multi-metal hydroxide structure and comprises cation laminates and anions between the laminates; the cation laminate elements comprise Ni, M, Al and O. The specific surface area, the active metal dispersity, the metal-carrier surface interface structure, the carrier acid-base sites and the like of the catalyst are changed by changing the composition proportion, the preparation method and the like of the doped metal M, so that the catalytic reaction performance is influenced. The invention also provides a catalyst for producing methane and a preparation method thereof, the active metal Ni in the NiMAl catalyst prepared by different methods, different M compositions and proportions and the like is good in dispersity, the electronic characteristics and geometric structure of a metal-carrier interface can be regulated and controlled, and the NiMAl catalyst has excellent performance at a lower reaction temperature; the catalyst can be popularized and applied to various catalytic reaction fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogenation catalysis, and in particular relates to a methane production catalyst and a preparation method and application thereof. Background Art

[0002] How to solve the environmental problems caused by the gradual depletion of non-renewable energy and its use is the focus of current attention. From a chemical perspective, carbon dioxide is a carbon resource with a wide range of sources and abundant and easily available. Researchers are working hard to convert carbon dioxide into chemicals with high added value, among which CO, CH4 and methanol are more studied. Methane, as the main component of natural gas, has the characteristics of high calorific value and low pollution after combustion. Therefore, it is a clean energy and is widely used in industries, energy and transportation.

[0003]

[0004] The CO2 methanation reaction is an exothermic process in thermodynamics, and low temperature is conducive to the forward reaction. However, low temperature is kinetically limited. Therefore, in order to achieve a high conversion rate and high selectivity of methane under low temperature conditions, an excellent catalyst is needed. In the reaction of producing methane by hydrogenation of carbon dioxide, nickel-based catalysts, as one of the commonly used catalysts, have high activity and high economic benefits, and therefore have been widely used. For example, the perovskite oxide-modified supported Ni-based catalyst reported in ZL202410280230.1 has a CO2 reaction conversion rate of up to 90% at a high temperature. In the relationship between conversion rate and time, it was found that the performance decreased to a certain extent after 100 hours; the Ni-La2O2CO3 catalyst reported in ZL202010563376.9 promoted the thermal stability, activity and selectivity of the reaction, but its reaction temperature was high and the equilibrium conversion rate was low, resulting in a low conversion rate, etc. However, the nickel-based catalysts obtained therefrom have some common problems, such as poor stability caused by easy sintering and carbon deposition at high temperatures, low dispersion of metal Ni, and poor performance at low temperatures. Summary of the invention

[0005] The object of the present invention is to provide a methane production catalyst, a preparation method and an application thereof. The hydrogenation catalyst of the present invention has high carbon dioxide activity at low temperature, high methane selectivity and high stability in the CO / CO2 hydrogenation to methane reaction.

[0006] The present invention provides an application of a hydrogenation catalyst in CO / CO2 hydrogenation to methane, wherein the hydrogenation catalyst is obtained by structural topological transformation and reduction of a catalyst precursor;

[0007] The catalyst precursor has a layered multi-metal hydroxide structure, including a cation layer formed by metal cations and anions between the layers; the metal elements in the cation layer include Ni, M and Al, and M includes one or more of Ce, Zr, In, Mg, Fe, Co, Zn, La, Ce, Mn, Ca, Sr, Ba, Y and Cu;

[0008] The temperature of the structural topological transformation is 200-1000° C., the time of the structural topological transformation is 0.1-48 hours, and the atmosphere of the structural topological transformation is one or more of vacuum, nitrogen, argon, helium, air and hydrogen.

[0009] Preferably, in the hydrogenation catalyst, the mass fraction of metal Ni is 0.1 to 70%, the mass fraction of metal M is 0.1 to 60%, and the mass fraction of metal Al is 0.1 to 60%.

[0010] Preferably, the reduction temperature is 200-800° C., the reduction pressure is 0.1-10 MPa, the reduction time is 1-12 hours, and the reduction atmosphere includes reducing gas or a mixed gas of reducing gas and protective gas.

[0011] The present invention provides a method for preparing a methane production catalyst, wherein the methane production catalyst is the hydrogenation catalyst in claim 1, and the hydrogenation catalyst is obtained by subjecting a catalyst precursor to structural topological transformation and reduction;

[0012] The catalyst precursor is prepared according to the pH method, comprising the following steps:

[0013] A1) mixing a nickel source, an M source, an aluminum source and water to obtain a mixed salt solution;

[0014] mixing a hydroxide-containing alkaline compound, a carbonate and water to obtain a mixed alkaline solution;

[0015] A2) mixing the mixed salt solution and the mixed alkali solution, controlling the pH value to be 6-14, and performing crystallization to obtain a catalyst precursor.

[0016] The present invention provides a method for preparing a methane production catalyst, wherein the methane production catalyst is the hydrogenation catalyst described above, and the hydrogenation catalyst is obtained by subjecting a catalyst precursor to structural topological transformation and reduction;

[0017] The catalyst precursor is prepared according to the in-situ growth method of alumina, comprising the following steps:

[0018] B1) mixing aluminum sulfate 18hydrate, a precipitant, sodium tartrate and water to obtain a first mixed solution, and crystallizing the first mixed solution under a constant temperature condition to obtain aluminum oxide;

[0019] B2) Mixing the nickel source, the M source, the aluminum oxide prepared in step B1), a precipitant and water to obtain a second mixed solution, and crystallizing the second mixed solution under a constant temperature condition to obtain a catalyst precursor.

[0020] The present invention provides a method for preparing a methane production catalyst, wherein the methane production catalyst is the hydrogenation catalyst mentioned above, and the hydrogenation catalyst is obtained by subjecting a catalyst precursor to structural topological transformation and reduction;

[0021] The catalyst precursor is prepared according to the foam metal in-situ growth method, which includes the following steps:

[0022] C1) mixing a nickel source, an M source, an aluminum source and water to obtain a mixed salt solution;

[0023] C2) mixing the mixed salt solution, the precipitant and the foamed metal, and crystallizing them under a constant temperature condition to obtain a catalyst precursor.

[0024] Preferably, the nickel source includes one or more of nickel nitrate hydrate, nickel sulfate and nickel chloride;

[0025] The aluminum source includes one or more of aluminum nitrate hydrate, aluminum chloride, aluminum sulfate and aluminum oxide;

[0026] The M source includes one or more of M nitrate, M oxide, M sulfate, M chloride and M acetylacetonate;

[0027] The hydroxide-containing alkaline compound includes sodium hydroxide and / or potassium hydroxide;

[0028] The carbonate includes one or more of sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate;

[0029] The precipitant includes one or more of urea, ammonium bicarbonate and oxalic acid.

[0030] Preferably, the molar ratio of the hydroxide-containing alkaline compound to the carbonate is (1-100):1;

[0031] The molar ratio of the precipitant to the total metal ions is (1-28):1.

[0032] The present invention provides a method for preparing a methane production catalyst, wherein the methane production catalyst is the hydrogenation catalyst mentioned above, and the hydrogenation catalyst can also be prepared according to a foam metal loading method, and the specific steps are as follows:

[0033] The catalyst precursor is subjected to structural topological transformation, and then the catalyst after structural topological transformation is dispersed in a solvent, injected into foamed metal, dried and then subjected to reduction treatment to obtain a hydrogenation catalyst.

[0034] The present invention provides a method for preparing a methane production catalyst, wherein the methane production catalyst is the hydrogenation catalyst mentioned above, and the hydrogenation catalyst can also be prepared by an atomic layer deposition method, and the specific steps are as follows:

[0035] The catalyst precursor is subjected to structural topological transformation, and then the catalyst after structural topological transformation is placed in an atomic layer deposition device, and a raw material gas containing M metal element and a diluent gas are introduced to perform atomic layer deposition to obtain a hydrogenation catalyst.

[0036] The present invention also provides a catalyst for producing methane, which is prepared according to the preparation method described above.

[0037] The present invention provides an application of a hydrogenation catalyst in CO / CO2 hydrogenation to methane, wherein the hydrogenation catalyst is obtained by structural topological transformation and reduction of a catalyst precursor; the catalyst precursor has a layered polymetallic hydroxide structure, including a cation layer formed by metal cations and anions between the layers; the metal elements in the cation layer include Ni, M and Al, and M includes one or more of Ce, Zr, In, Mg, Fe, Co, Zn, La, Ce, Mn, Ca, Sr, Ba, Y and Cu; the temperature of the structural topological transformation is 200 to 1000°C, the time of the structural topological transformation is 0.1 to 48 hours, and the atmosphere of the structural topological transformation is one or more of vacuum, nitrogen, argon, helium, air and hydrogen. The present invention utilizes methods such as adjustable ratio of metal element types in the layer, adjustable anions between layers, and orderly arrangement of metal atoms in the layer to dope M to form a layered polymetallic hydroxide, and the M element in the obtained catalyst is evenly dispersed, and there is a strong interaction between the metal Ni and the composite metal oxide carrier MA1O. The specific surface area of ​​the catalyst, the surface and interface structure, and the acid-base sites on the catalyst are changed by doping with different M, thus affecting the catalytic reaction performance. In addition, the NiMAl catalyst prepared by different methods has good dispersion of the active metal Ni, and the electronic properties and geometric structure of the metal-support interface can be adjusted. When it is used for one or more co-hydrogenation reactions of CO and CO2 or their co-hydrogenation reactions in a hydrogen sulfide atmosphere, it has excellent performance and good stability at a lower reaction temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0039] Figure 1 XRD diagrams of NiAl-9-LDHs, NiZrAl-1-LDHs, NiZrAl-2-LDHs and NiZrAl-3-LDHs catalysts of the present invention;

[0040] Figure 2 XRD diagrams of NiAl-9, NiZrAl-1, NiZrAl-2 and NiZrAl-3 catalysts of the present invention;

[0041] Figure 3 These are transmission electron microscope (TEM) images of the NiAl-9, NiZrAl-1, NiZrAl-2 and NiZrAl-3 catalysts of the present invention, wherein Figure a is the NiAl-9 catalyst, Figure b is the NiZrAl-1 catalyst, Figure c is the NiZrAl-2 catalyst, and Figure d is the NiZrAl-3 catalyst. DETAILED DESCRIPTION

[0042] The present invention provides an application of a hydrogenation catalyst in CO / CO2 hydrogenation to methane, characterized in that the hydrogenation catalyst is obtained by structural topological transformation and reduction of a catalyst precursor;

[0043] The catalyst precursor has a layered multi-metal hydroxide structure, including a cation layer formed by metal cations and anions between the layers; the metal elements in the cation layer include Ni, M and Al, and M includes one or more of Ce, Zr, In, Mg, Fe, Co, Zn, La, Ce, Mn, Ca, Sr, Ba, Y and Cu;

[0044] The temperature of the structural topological transformation is 200-1000° C., the time of the structural topological transformation is 0.1-48 hours, and the atmosphere of the structural topological transformation is one or more of vacuum, nitrogen, argon, helium, air and hydrogen.

[0045] In the present invention, the hydrogenation catalyst has a layered structure and has a structure in which the active metal Ni is partially coated with the oxide of M. The structure can form a metal-support interface structure and has a metal-support interaction (MSI). It can also realize the metal oxide coating of metal particles, thereby preventing the Ni particle size from increasing continuously during the reaction, inhibiting the sintering deactivation of the catalyst, and providing stability. At the same time, the structure has a higher specific surface area and more basic sites, and the Ni and M elements are evenly dispersed. There is an interaction between the active metal Ni and the composite metal oxide support, which can change the metal charge density, thereby improving the catalytic activity.

[0046] In the present invention, in the hydrogenation catalyst, the mass fraction of metal Ni is 0.1 to 70%, more preferably 1 to 65%, such as 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, preferably a range value with any of the above values ​​as the upper or lower limit, and the mass fraction of metal M is 0.1 to 60%, more preferably 1 to 55%, such as 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, preferably a range value with any of the above values ​​as the upper or lower limit, the mass fraction of metal Al is preferably 0.1-60%, more preferably 1-55%, such as 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, preferably a range value with any of the above values ​​as the upper or lower limit.

[0047] In the present invention, the molar ratio of divalent cations to high-valent cations in the hydrogenation catalyst is preferably (1-6):1, more preferably (1-4):1, such as 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, preferably a range value with any of the above values ​​as the upper or lower limit; the high-valent cations preferably include trivalent cations and / or tetravalent cations.

[0048] In the present invention, the catalyst precursor has a layered multimetal hydroxide structure, including a cationic layer formed by metal cations and anions between the layers; the metal elements in the cationic layer preferably include Ni, M and Al, M includes one or more of Ce, Zr, In, Mg, Fe, Co, Zn, La, Ce, Mn, Ca, Sr, Ba, Y and Cu; the anions between the layers are preferably OH - and / or CO3 2- .

[0049] In the present invention, the three metal cations of Ni, M and Al have an atomic-level arrangement structure in the cation layer, and the thickness of the single layer of the cation layer is preferably 1 to 10 nm.

[0050] In the present invention, the catalyst precursor can be prepared by a pH method, an alumina in-situ growth method, or a nickel foam in-situ growth method.

[0051] pH Method

[0052] In the present invention, the catalyst precursor is prepared by a pH method, and the specific steps are as follows:

[0053] A1) mixing a nickel source, an M source, an aluminum source and water to obtain a mixed salt solution;

[0054] mixing a hydroxide-containing alkaline compound, a carbonate and water to obtain a mixed alkaline solution;

[0055] A2) mixing the mixed salt solution and the mixed alkali solution, controlling the pH value to be 6-14, and performing crystallization to obtain a catalyst precursor.

[0056] In the present invention, the nickel source includes one or more of nickel nitrate hydrate, nickel sulfate and nickel chloride; the aluminum source includes one or more of aluminum nitrate hydrate, aluminum chloride and aluminum oxide; the M source includes one or more of M nitrate, M oxide, M sulfate, M chloride and M acetylacetonate; the ratio of the nickel source, M source and aluminum source in the present invention can be adjusted according to the ratio of Ni, M and Al in the hydrogenation catalyst, and the present invention does not specifically limit this.

[0057] In the present invention, the hydroxide-containing alkaline compound includes sodium hydroxide and / or potassium hydroxide; the carbonate includes sodium carbonate and / or potassium carbonate; the molar ratio of the hydroxide-containing alkaline compound to the carbonate is preferably (1-100):1, more preferably (1-50):1, such as 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, preferably any of the above values ​​is used as the upper or lower limit range value; in the mixed alkaline solution, the sum of the molar concentrations of the hydroxide-containing alkaline compound and the carbonate is preferably 0.01 to 5 mol / L, more preferably 0.1 to 1 mol / L, such as 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L, 5 mol / L, preferably a range value with any of the above values ​​as the upper or lower limit.

[0058] After obtaining the mixed salt solution and the mixed alkali solution, the present invention mixes the mixed salt solution and the mixed alkali solution, and controls the pH value to be 6-14, preferably 8-13, such as pH 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, preferably a range value with any of the above values ​​as the upper or lower limit; preferably, the mixed salt solution and the mixed alkali solution are respectively added dropwise to deionized water, and the pH of the mixed system of the three is controlled to be between 8 and 13. After all the mixed salt solutions are added dropwise, the mixed system is transferred to a constant temperature water bath environment, and crystallized under constant temperature conditions to obtain a catalyst precursor.

[0059] In the present invention, the volume ratio of the mixed salt solution and the mixed alkali solution is preferably (0.1-5):1; more preferably (0.5-2):1. In some specific embodiments of the present invention, the volume ratio of the mixed salt solution and the mixed alkali solution is 1:1; the present invention preferably controls the pH of the mixed system to be between 8 and 13, more preferably 8.5-10, such as controlling the pH to 8, 9, 10, 11, 12 or 13, and in the process of mixing the mixed salt solution and the mixed alkali solution, the pH value of the system is controlled to remain unchanged, specifically, the pH value can be controlled to remain unchanged by controlling the dropping acceleration and the stirring speed. Preferably, the present invention monitors the pH value of the system by a pH meter and controls it to remain unchanged, thereby ensuring that the catalyst precursor has suitable alkaline properties, thereby reducing the problem of carbon deposition and deactivation of the catalyst occurring during the hydrogenation reaction.

[0060] In the present invention, the crystallization temperature is preferably 40-100°C, more preferably 50-80°C, such as 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, preferably a range value with the above arbitrary numerical values ​​as the upper or lower limit; the crystallization time is preferably 6-24 hours, more preferably 8-20 hours, such as 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, preferably a range value with the above arbitrary numerical values ​​as the upper or lower limit.

[0061] After the crystallization is completed, the crystallized reaction liquid is subjected to solid-liquid separation, and the separated solid is washed with water, a mixed solution of anhydrous ethanol and acetone, and then dried to obtain a catalyst precursor.

[0062] In the present invention, it is preferred to use deionized water to wash the separated solid to neutrality (pH 7-7.5). The present invention has no particular limitation on the washing method described in the above preparation method, and it can be a method well known to those skilled in the art such as centrifugation, vacuum filtration, and normal pressure filtration.

[0063] In the present invention, the drying temperature is preferably 30 to 200°C, more preferably 50 to 150°C, such as 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, preferably a range value with any of the above values ​​as the upper or lower limit; the drying time is preferably 1 to 48 hours, more preferably 5 to 40 hours. The present invention has no particular limitation on the drying method, which can be methods well known to those skilled in the art such as atmospheric pressure drying, vacuum drying, and freeze drying.

[0064] Alumina in situ growth method

[0065] In the present invention, the catalyst precursor can be prepared according to the alumina in-situ growth method, and the specific steps are as follows:

[0066] B1) mixing aluminum sulfate 18hydrate, a precipitant, a complexing agent sodium tartrate and water to obtain a first mixed solution, and crystallizing the first mixed solution under a constant temperature condition to obtain aluminum oxide;

[0067] B2) Mixing the nickel source, the M source, the aluminum oxide prepared in step B1), a precipitant and water to obtain a second mixed solution, and crystallizing the second mixed solution under a constant temperature condition to obtain a catalyst precursor.

[0068] In the present invention, the precipitant is preferably one or more of urea, ammonium bicarbonate and oxalic acid; in the first mixed solution, the molar ratio of the precipitant to the total metal ions in the first mixed solution is preferably (1-28):1, more preferably (10-20):1, such as 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1 1, 27:1, 28:1, preferably a range value with any of the above values ​​as the upper or lower limit; the complexing agent is preferably sodium tartrate, and the sodium tartrate reacts with aluminum ions in an alkaline solution to facilitate the precipitation and separation of alumina. The molar ratio of the complexing agent to aluminum sulfate 18hydrate is preferably 1:(1-15), more preferably 1:(5-10), such as 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, preferably a range value with any of the above values ​​as the upper or lower limit.

[0069] After obtaining the first mixed solution, the present invention transfers the first mixed solution to a reaction kettle and performs crystallization under constant temperature conditions. After the crystallization is completed, solid-liquid separation is performed, and the separated solid is dried to obtain aluminum oxide.

[0070] In the present invention, the crystallization temperature of the first mixed solution is preferably 90-150°C, more preferably 100-120°C, such as 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, preferably a range value with any of the above values ​​as the upper or lower limit; the crystallization time of the first mixed solution is preferably 9-24 hours, more preferably 10-20 hours.

[0071] In the present invention, the drying temperature is preferably 30 to 200°C, more preferably 50 to 150°C, such as 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, preferably a range value with any of the above values ​​as the upper or lower limit; the drying time is preferably 1 to 48 hours, more preferably 5 to 40 hours. The present invention has no particular limitation on the drying method, which can be methods well known to those skilled in the art such as atmospheric pressure drying, vacuum drying, and freeze drying.

[0072] The aluminum oxide prepared in the present invention has a spherical morphology, specifically a small spherical morphology formed by stacking multiple layers of aluminum oxide flakes.

[0073] After obtaining alumina, the present invention mixes the nickel source, M source, alumina and a precipitant in water to obtain a second mixed solution, transfers the second mixed solution to a hydrothermal kettle, crystallizes the solution under constant temperature conditions, performs solid-liquid separation on the crystallized reaction solution, and sequentially washes the separated solid with water and anhydrous ethanol / acetone solution, and then dries the solution to obtain a catalyst precursor.

[0074] In the present invention, the nickel source includes one or more of nickel nitrate hydrate, nickel sulfate and nickel chloride; the M source includes one or more of M nitrate, M oxide, M sulfate, M chloride and M acetylacetonate; the ratio of the nickel source, M source and alumina in the present invention can be adjusted according to the ratio of Ni, M and Al in the hydrogenation catalyst, and the present invention does not specifically limit this.

[0075] In the present invention, the precipitant is preferably one or more of urea, ammonium bicarbonate and oxalic acid; in the second mixed solution, the molar ratio of the precipitant to the total metal ions in the second mixed solution is preferably (1-28):1, more preferably (10-20):1, such as 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1, 27:1, 28:1, preferably a range value with any of the above values ​​as the upper or lower limit.

[0076] In the present invention, the crystallization temperature of the second mixed solution is preferably 90-150°C, more preferably 100-120°C, such as 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, preferably a range value with any of the above values ​​as the upper or lower limit; the crystallization time of the second mixed solution is preferably 9-24 hours, more preferably 10-20 hours.

[0077] After the crystallization is completed, the crystallized reaction liquid is subjected to solid-liquid separation, and the separated solid is washed with water and anhydrous ethanol / acetone solution in sequence, and then dried to obtain a catalyst intermediate.

[0078] In the present invention, it is preferred to use deionized water to wash the separated solid to neutrality (pH 7-7.5). The present invention has no particular limitation on the washing method described in the above preparation method, and it can be a method well known to those skilled in the art such as centrifugation, vacuum filtration, and normal pressure filtration.

[0079] In the present invention, the drying temperature is preferably 30 to 200°C, more preferably 50 to 150°C, such as 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, preferably a range value with any of the above values ​​as the upper or lower limit; the drying time is preferably 1 to 48 hours, more preferably 5 to 40 hours. The present invention has no particular limitation on the drying method, which can be methods well known to those skilled in the art such as atmospheric pressure drying, vacuum drying, and freeze drying.

[0080] In-situ growth of metal foam

[0081] In the present invention, the catalyst precursor can also be prepared by an in-situ growth method of a foamed metal, which specifically comprises the following steps:

[0082] C1) mixing a nickel source, an M source, an aluminum source and water to obtain a mixed salt solution;

[0083] C2) mixing the mixed salt solution, the precipitant and the foamed metal, and crystallizing them under a constant temperature condition to obtain a catalyst precursor.

[0084] Preferably, in the present invention, a nickel source, an M source, an aluminum source and water are mixed to obtain a mixed salt solution; a precipitant and water are mixed to obtain a precipitant solution; then the mixed salt solution, the precipitant solution and the foamed metal are mixed to obtain a mixed solution, and the mixed solution is crystallized under constant temperature conditions to obtain a catalyst precursor.

[0085] In the present invention, the nickel source includes one or more of nickel nitrate hydrate, nickel sulfate and nickel chloride; the aluminum source includes one or more of aluminum nitrate hydrate, aluminum chloride and aluminum oxide; the M source includes one or more of M nitrate, M oxide, M sulfate, M chloride and M acetylacetonate; the ratio of the nickel source, M source and aluminum source in the present invention can be adjusted according to the ratio of Ni, M and Al in the hydrogenation catalyst, and the present invention does not specifically limit this.

[0086] In the present invention, the precipitant is preferably one or more of urea, ammonium bicarbonate and oxalic acid; in the mixed solution, the molar ratio of the precipitant to the total metal ions in the mixed solution is preferably (1-28):1, more preferably (10-20):1, such as 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1 3:1, 24:1, 25:1, 26:1, 27:1, 28:1, preferably a range value with any of the above values ​​as the upper or lower limit; the foam metal is preferably foam nickel and / or foam iron, and the mass ratio of the foam metal to the catalyst after topological structure conversion is preferably (0.1-10):1, more preferably (2-8):1, such as 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, preferably a range value with any of the above values ​​as the upper or lower limit.

[0087] In the present invention, the volume ratio of the mixed salt solution to the precipitant solution is preferably (0.1-5):1, and more preferably (0.5-2):1. In some specific embodiments of the present invention, the volume ratio of the mixed salt solution to the mixed alkali solution is 1:1.

[0088] In the present invention, the crystallization temperature is preferably 90-180°C, more preferably 100-150°C, such as 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, preferably a range value with any of the above values ​​as the upper or lower limit; the crystallization time is preferably 1 to 24 hours, more preferably 5 to 20 hours.

[0089] After the crystallization is completed, the present invention performs solid-liquid separation on the crystallization reaction liquid, washes the separated solid with deionized water until it is neutral (pH value is 7 to 7.5), and then dries it to obtain a catalyst precursor. The present invention has no particular limitation on the washing method described in the above preparation method, and can be a method well known to those skilled in the art such as centrifugation, vacuum filtration, and normal pressure filtration.

[0090] In the present invention, the drying temperature is preferably 30 to 200°C, more preferably 50 to 150°C, such as 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, preferably a range value with any of the above values ​​as the upper or lower limit; the drying time is preferably 1 to 48 hours, more preferably 5 to 40 hours. The present invention has no particular limitation on the drying method, which can be methods well known to those skilled in the art such as atmospheric pressure drying, vacuum drying, and freeze drying.

[0091] After obtaining the catalyst precursor, the present invention sequentially performs structural topological transformation and reduction treatment on the catalyst precursor to obtain a hydrogenation catalyst.

[0092] In the present invention, the temperature of the structural topological transformation is preferably 200-800°C, more preferably 300-700°C, such as 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, preferably a range value with any of the above values ​​as the upper or lower limit; the time of the structural topological transformation is preferably 1-12 hours, more preferably 2-6 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, preferably a range value with any of the above values ​​as the upper or lower limit; the atmosphere of the structural topological transformation is preferably one or more of vacuum, nitrogen, argon, helium and air, more preferably air atmosphere; after the structural topological transformation, the ions in the precursor such as CO3 2- OH - Ions gradually turn into CO2 and water and separate with the process of structural topological transformation, and finally form mixed metal oxides (non-reducing atmosphere) or mixed metals (reducing atmosphere). The catalyst obtained after the structural topological transformation process still has a layered structure.

[0093] In the present invention, the temperature of the reduction treatment is preferably 200-800°C, more preferably 300-700°C, such as 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, preferably a range value with the above arbitrary numerical value as the upper or lower limit; the time of the reduction treatment is preferably 1-12 hours, more preferably 2-6 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, preferably a range value with the above arbitrary numerical value as the upper or lower limit.

[0094] The atmosphere of the reduction treatment is preferably a reducing atmosphere, and the reducing atmosphere includes a reducing gas, and the reducing gas is preferably one or more of hydrogen, methane and ammonia. Preferably, the reducing atmosphere may also include a protective atmosphere such as nitrogen and / or argon. Preferably, in the reducing atmosphere, the volume fraction of the reducing gas is preferably 5% to 100%, more preferably 10% to 50%, such as 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 70%, 80%, 90%, 100%, preferably a range value with any of the above values ​​as the upper or lower limit. The pressure of the reduction treatment is preferably 0.1 to 10 MPa, more preferably 1 to 8 MPa, such as 0.1 MPa, 0.5 MPa, 1 MPa, 2 MPa, 3 MPa, 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, 10 MPa, preferably a range value with any of the above values ​​as the upper or lower limit.

[0095] After the catalyst precursor is obtained in the present invention, it can be directly subjected to structural topological transformation and reduction treatment to obtain a hydrogenation catalyst, or it can be prepared according to the following foam metal loading method.

[0096] Metal foam loading method

[0097] In the present invention, the hydrogenation catalyst can also be prepared according to a foam metal supporting method, which specifically comprises the following steps:

[0098] D1) preparing a catalyst precursor according to any one of the pH method, alumina in-situ growth method or metal foam in-situ growth method described above;

[0099] D2) performing structural topological transformation on the catalyst precursor, dispersing the catalyst after structural topological transformation in a solvent, injecting foam metal, drying and performing reduction treatment to obtain a hydrogenation catalyst.

[0100] In the present invention, the temperature of the structural topological transformation is preferably 200-800°C, more preferably 300-700°C, such as 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, preferably a range value with any of the above values ​​as the upper or lower limit; the time of the structural topological transformation is preferably 1-12 hours, more preferably 2-6 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, preferably a range value with any of the above values ​​as the upper or lower limit; the atmosphere of the structural topological transformation is preferably one or more of vacuum, nitrogen, argon, helium and air, more preferably air atmosphere; after the structural topological transformation, the ions in the precursor such as CO3 2- OH - Ions gradually turn into CO2 and water and separate with the process of structural topological transformation, and finally form mixed metal oxides (non-reducing atmosphere) or mixed metals (reducing atmosphere). The catalyst obtained after the structural topological transformation process still has a layered structure.

[0101] After obtaining the catalyst after structural topology transformation, the present invention mixes it with a solvent, injects it into foamed metal, and performs reduction treatment after drying to obtain a hydrogenation catalyst.

[0102] In the present invention, the solvent is preferably ethanol, and the foam metal is preferably foam nickel and / or foam iron; the mass ratio of the foam metal to the catalyst after topological structure conversion is preferably (0.1-10):1, more preferably (2-8):1, such as 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, preferably a range value with any of the above values ​​as the upper or lower limit.

[0103] In the present invention, the drying temperature is preferably 30 to 200°C, more preferably 50 to 150°C, such as 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, preferably a range value with any of the above values ​​as the upper or lower limit; the drying time is preferably 1 to 48 hours, more preferably 5 to 40 hours. The present invention has no particular limitation on the drying method, which can be methods well known to those skilled in the art such as atmospheric pressure drying, vacuum drying, and freeze drying.

[0104] In the present invention, the temperature of the reduction treatment is preferably 200-800°C, more preferably 300-700°C, such as 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, preferably a range value with the above arbitrary numerical value as the upper or lower limit; the time of the reduction treatment is preferably 1-12 hours, more preferably 2-6 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, preferably a range value with the above arbitrary numerical value as the upper or lower limit.

[0105] The atmosphere of the reduction treatment is preferably a reducing atmosphere, and the reducing atmosphere includes a reducing gas, and the reducing gas is preferably one or more of hydrogen, methane and ammonia. Preferably, the reducing atmosphere may also include a protective atmosphere such as nitrogen and / or argon. Preferably, in the reducing atmosphere, the volume fraction of the reducing gas is preferably 5% to 100%, more preferably 10% to 50%, such as 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 70%, 80%, 90%, 100%, preferably a range value with any of the above values ​​as the upper or lower limit. The pressure of the reduction treatment is preferably 0.1 to 10 MPa, more preferably 1 to 8 MPa, such as 0.1 MPa, 0.5 MPa, 1 MPa, 2 MPa, 3 MPa, 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, 10 MPa, preferably a range value with any of the above values ​​as the upper or lower limit.

[0106] Atomic layer deposition

[0107] In the present invention, the hydrogenation catalyst can be prepared by atomic layer deposition, and the specific steps are as follows:

[0108] E1) mixing a nickel source, an aluminum source and water to obtain a mixed salt solution;

[0109] mixing a hydroxide-containing alkaline compound, a carbonate and water to obtain a mixed alkaline solution;

[0110] E2) mixing the mixed salt solution and the mixed alkali solution, controlling the pH value to be 8 to 13, and performing crystallization to obtain a catalyst precursor;

[0111] E3) performing structural topological transformation on the catalyst precursor, and then placing the catalyst precursor after structural topological transformation in an atomic layer deposition device, introducing a raw material gas containing metal M and a diluent gas, performing atomic layer deposition, and obtaining a hydrogenation catalyst.

[0112] In the present invention, the nickel source includes one or more of nickel nitrate hydrate, nickel sulfate and nickel chloride; the aluminum source includes one or more of aluminum nitrate hydrate, aluminum chloride and aluminum oxide; the ratio of the nickel source to the aluminum source in the present invention can be adjusted according to the ratio of Ni, M and Al in the hydrogenation catalyst, and the present invention does not specifically limit this.

[0113] In the present invention, the hydroxide-containing alkaline compound includes sodium hydroxide and / or potassium hydroxide; the carbonate includes sodium carbonate and / or potassium carbonate; the molar ratio of the hydroxide-containing alkaline compound to the carbonate is (1-100):1, more preferably (1-50):1, such as 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, preferably any of the above values ​​as the upper or lower limit. Range value; in the mixed alkaline solution, the sum of the molar concentrations of the hydroxide-containing alkaline compound and the carbonate is preferably 0.01-5 mol / L, more preferably 0.1-1 mol / L, such as 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L, 5 mol / L, preferably a range value with any of the above values ​​as the upper or lower limit.

[0114] After obtaining the mixed salt solution and the mixed alkali solution, the present invention mixes the mixed salt solution and the mixed alkali solution to control the pH value to be 8-13; preferably, the mixed salt solution and the mixed alkali solution are respectively added dropwise to deionized water to control the pH value of the mixed system of the three to be between 8 and 13. After all the mixed salt solutions are added dropwise, the mixed system is transferred to a constant temperature water bath environment and crystallized under constant temperature conditions to obtain a catalyst intermediate.

[0115] In the present invention, the volume ratio of the mixed salt solution and the mixed alkali solution is preferably (0.1-5):1; more preferably (0.5-2):1. In some specific embodiments of the present invention, the volume ratio of the mixed salt solution and the mixed alkali solution is 1:1; it is sufficient to ensure that the pH of the mixed system is between 8 and 13, and more preferably 8.5-10, such as controlling the pH at 8, 9, 10, 11, 12 or 13. During the mixing of the mixed salt solution and the mixed alkali solution, the pH value of the system is controlled to remain unchanged, specifically, the pH value can be controlled to remain unchanged by controlling the dropping acceleration and the stirring speed. Preferably, the present invention monitors the pH value of the system by a pH meter and controls it to remain unchanged, thereby ensuring that the catalyst precursor has suitable alkaline properties, thereby reducing the problem of carbon deposition and deactivation of the catalyst occurring during the hydrogenation reaction.

[0116] In the present invention, the crystallization temperature is preferably 40-100°C, more preferably 50-80°C, such as 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, preferably a range value with the above arbitrary numerical values ​​as the upper or lower limit; the crystallization time is preferably 6-24 hours, more preferably 8-20 hours, such as 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, preferably a range value with the above arbitrary numerical values ​​as the upper or lower limit.

[0117] After the crystallization is completed, the crystallized reaction liquid is subjected to solid-liquid separation, and the separated solid is washed with water, a mixed solution of anhydrous ethanol and acetone, and then dried to obtain a catalyst precursor.

[0118] In the present invention, it is preferred to use deionized water to wash the separated solid to neutrality (pH 7-7.5). The present invention has no particular limitation on the washing method described in the above preparation method, and it can be a method well known to those skilled in the art such as centrifugation, vacuum filtration, and normal pressure filtration.

[0119] In the present invention, the drying temperature is preferably 30 to 200°C, more preferably 50 to 150°C, such as 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, preferably a range value with any of the above values ​​as the upper or lower limit; the drying time is preferably 1 to 48 hours, more preferably 5 to 40 hours. The present invention has no particular limitation on the drying method, which can be methods well known to those skilled in the art such as atmospheric pressure drying, vacuum drying, and freeze drying.

[0120] After obtaining the catalyst precursor, the present invention performs structural topological transformation on the catalyst precursor to obtain a catalyst precursor after structural topological transformation.

[0121] In the present invention, the temperature of the structural topological transformation is preferably 200-800°C, more preferably 300-700°C, such as 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, preferably a range value with any of the above values ​​as the upper or lower limit; the time of the structural topological transformation is preferably 1-12 hours, more preferably 2-6 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, preferably a range value with any of the above values ​​as the upper or lower limit; the atmosphere of the structural topological transformation is preferably one or more of vacuum, nitrogen, argon, helium and air, more preferably air atmosphere; after the structural topological transformation, the ions in the precursor such as CO3 2- OH - Ions gradually turn into CO2 and water and separate with the process of structural topological transformation, and finally form mixed metal oxides (non-reducing atmosphere) or mixed metals (reducing atmosphere). The catalyst obtained after the structural topological transformation process still has a layered structure.

[0122] After obtaining the catalyst precursor after the structural topology transformation, the present invention places it in an atomic layer deposition device, introduces raw material gas and diluent gas, performs atomic layer deposition, and obtains the catalyst precursor.

[0123] In the present invention, the raw gas is a raw gas containing M metal elements, such as inorganic metal precursors such as M halides, or precursors of organic metal M such as alkyl, cyclopentadienyl, alkoxide, β-diketone, alkylamine, silanamine and amide; the diluent gas is preferably one or more of nitrogen, argon and helium, and the volume ratio of the raw gas to the diluent gas is preferably (0.1-10):1, more preferably (2-8):1, such as 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, preferably a range value with any of the above values ​​as the upper or lower limit.

[0124] In the present invention, the temperature of the atomic layer deposition is preferably 50-200°C, more preferably 100-150°C, such as 50°C, 80°C, 100°C, 120°C, 150°C, 180°C, 200°C, preferably a range value with any of the above values ​​as the upper or lower limit. After depositing a layer of M metal layer, the present invention uses a purge gas for purge, such as one or more of nitrogen, argon and helium, and then deposits multiple times until the desired deposition amount or deposition thickness is reached.

[0125] In the above-mentioned five preparation methods, namely, pH method, alumina in-situ growth method, metal foam in-situ growth method, metal foam in-situ loading method and atomic layer deposition method, the water used is preferably one or more of distilled water, deionized water and ultrapure water, more preferably deionized water.

[0126] The present invention applies the hydrogenation catalyst prepared by the above method to the reaction of CO / CO2 hydrogenation to methane. The NiMAl hydrogenation catalyst prepared by the above preparation method is used as a hydrogenation catalyst, which is directly contacted with the reaction gas containing CO / CO2 and H2 to react and obtain methane and water.

[0127] In the present invention, the "CO / CO2" refers to CO and / or CO2. The present invention has no special limitation on the reactor for the above-mentioned CO / CO2 hydrogenation reaction to prepare methane, and it can be a fixed bed reactor.

[0128] In the present invention, the volume ratio of CO / CO2 to H2 in the reaction gas is preferably (1-6):1; more preferably (3-5):1, such as 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, preferably a range value with any of the above values ​​as the upper or lower limit. The volume flow rate of the mixed gas of CO / CO2 and H2 is preferably 20-160mL / min, more preferably 50-150mL / min, such as 20mL / min, 30mL / min, 40mL / min, 50mL / min, 60mL / min, 70mL / min, 80mL / min, 90mL / min, 100mL / min, 110mL / min, 120mL / min, 130mL / min, 140mL / min, 150mL / min, 160mL / min, preferably a range value with any of the above values ​​as the upper or lower limit.

[0129] In the present invention, a diluent gas is preferably introduced into the hydrogenation reaction to dilute and regulate the concentration of the reaction gas. The diluent gas is preferably one or more of nitrogen, argon and helium. The volume ratio of the diluent gas to the reaction gas (CO / CO2 and H2) is preferably 1:(3-5), more preferably 1:4.

[0130] In the present invention, the reaction temperature of the CO / CO2 hydrogenation to methane is preferably 100-700°C, more preferably 200-300°C, such as 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, preferably a range value with any of the above values ​​as the upper or lower limit; specifically, in an embodiment of the present invention, the reaction temperature of the CO / CO2 hydrogenation to methane is 300°C, which is beneficial to reduce side reactions caused by overheating.

[0131] In the present invention, the mass space velocity of the CO / CO2 hydrogenation reaction to produce methane is preferably 4000 to 600000 mL / g cat / h, more preferably 10000 to 100000 mL / g cat / h, such as 4000mL / g cat / h, 8000mL / g cat / h, 10000mL / g cat / h, 50000mL / g cat / h, 100000mL / g cat / h, 200000mL / g cat / h, 300000mL / g cat / h, 400000mL / g cat / h, 500000mL / g cat / h, 600000mL / g cat / h, preferably a range value with any of the above numerical values ​​as the upper limit or the lower limit.

[0132] In the present invention, the pressure of the CO / CO2 hydrogenation reaction to produce methane is preferably 0.1-10 MPa; more preferably 0.1-0.5 MPa, such as 0.1 MPa, 0.5 MPa, 1 MPa, 2 MPa, 3 MPa, 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, 10 MPa, preferably a range value with any of the above values ​​as the upper or lower limit.

[0133] The present invention uses nickel salt, M salt and aluminum salt as raw materials, uses hydroxide-containing alkaline compounds and carbonate aqueous solutions as precipitants, or uses urea, ammonium bicarbonate or oxalic acid as precipitants, and adopts pH method, atomic layer deposition method, alumina in-situ growth method, foam metal loading method and foam metal in-situ growth method to prepare, and obtains a layered NiMAl catalyst. The preparation method of the present invention utilizes adjustable layered metal elements to dope M elements to form a layered multi-metal hydroxide precursor, and the M elements in the obtained catalyst are evenly dispersed, and there is a strong interaction between the active metal Ni and the composite metal oxide carrier MA1O. The specific surface area of ​​the catalyst and the alkaline sites on the catalyst are changed by doping with different M, thereby affecting the catalytic activity. In addition, the NiMAl catalyst prepared by different methods has good dispersibility of the active metal Ni, and the metal-carrier interface promotes adjustable electronic properties. When it is used for CO / CO2 hydrogenation reaction, it has excellent performance and good stability at a relatively low temperature.

[0134] In order to further illustrate the present invention, a methane production catalyst provided by the present invention, a preparation method thereof and an application thereof are described in detail below in conjunction with embodiments, but it should not be construed as limiting the scope of protection of the present invention.

[0135] Example 1

[0136] (I) Preparation of NiCeAl-1 catalyst

[0137] Nickel nitrate hydrate, cerium nitrate hydrate and aluminum nitrate hydrate were added at a molar ratio of divalent cations to (trivalent cations + tetravalent cations) of 1:1, and deionized water was used as a solvent. They were fully stirred to completely dissolve and prepare 100 mL of a mixed salt solution of about 0.5 mol / L.

[0138] Prepare 100mL of 0.2mol / L mixed alkaline solution of sodium hydroxide and sodium carbonate and stir thoroughly to dissolve them completely.

[0139] In another beaker, add 50 mL of distilled water, slowly drip the alkaline solution and salt solution into it, and continue to stir. Use a pH meter to control the pH of the suspension to 9.5 ± 0.5. After all the salt solutions have been added, move the suspension into a constant temperature water bath, control the crystallization temperature to 90 ° C, and continue to stir for 12 hours.

[0140] After the crystallization is completed, the solid-liquid separation is performed, and the solid is washed with deionized water until it is neutral, and then the solid is placed in a 60° C. constant temperature oven to dry for 3 to 24 hours. The catalyst precursor is obtained.

[0141] The obtained solid powder was further treated for structural topological transformation at 550 °C for 4 h, and finally heated at 550 °C with a total flow rate of 50 mL min-1 , and reduced in a mixed gas of H2:N2 at a ratio of 5:45 for 2 h to obtain a Ni-based catalyst NiCeAl-1 with a layered structure.

[0142] In the NiCeAl-1 catalyst provided in this embodiment, based on the mass of the catalyst being 100%, the mass content of Ni is 50wt%, and the mass content of metal Ce is 10wt%.

[0143] (II) NiCeAl-1 catalyst for hydrogenation of carbon dioxide to methane

[0144] 0.1 g of NiCeAl-1 catalyst was weighed and placed in a quartz reaction tube, and a hydrogen-nitrogen mixed gas with a total volume flow rate of 50 mL / min and a hydrogen volume concentration of 10% was introduced, and reduction pretreatment was performed at 550° C. for 2 h. After the reduction pretreatment was completed, the H2 gas was turned off.

[0145] The mixed reaction gas (CO2+H2+N2, the volume ratio of CO2, H2 and N2 is 18:72:10) is introduced and pressurized to 0.33MPa, the temperature is raised to 300℃, and the mixed gas flow rate is adjusted to 50mL·min -1 .

[0146] Reaction product monitoring: During the reaction process, the products of different reaction times are analyzed. The detection method is: after the reaction reaches a steady state, the products of the reaction system are collected every 20 minutes.

[0147] The obtained carbon dioxide reaction rate, methane selectivity and space-time yield are shown in Table 1.

[0148] Example 2

[0149] (I) Preparation of NiTiAl-2 catalyst

[0150] 1) Nickel nitrate hydrate and aluminum nitrate hydrate are added at a molar ratio of divalent cations to trivalent cations of 1:1, and deionized water is used as a solvent. They are fully stirred to completely dissolve and prepare 100 mL of a mixed salt solution of about 0.5 mol / L.

[0151] Prepare 100mL of 0.2mol / L mixed alkaline solution of sodium hydroxide and sodium carbonate and stir thoroughly to dissolve them completely.

[0152] In another beaker, add 50 mL of distilled water, slowly drip the alkaline solution and salt solution into it, and continue to stir. Use a pH meter to control the pH of the suspension to 9.5 ± 0.5. After all the salt solutions have been added, move the suspension into a constant temperature water bath, control the crystallization temperature to 90 ° C, and continue to stir for 12 hours.

[0153] After the crystallization is completed, the solid-liquid separation is performed, and the solid is washed with deionized water until it is neutral, and then the solid is placed in a 60° C. constant temperature oven to dry for 3 to 24 hours to obtain a NiAl catalyst precursor.

[0154] The obtained NiAl catalyst precursor underwent a structural topological transformation at 550°C for 4 hours, and finally a NiAl-MMO catalyst was obtained.

[0155] The obtained nickel-aluminum catalyst was introduced into TiO2 by atomic layer deposition (ALD). The specific steps were as follows: open the carrier gas nitrogen, above 0.4Mpa, open the vacuum valve to evacuate, turn on the heating control button, heat to 150°C, wait for the temperature to stabilize for about 5 minutes, then fill with titanium tetrachloride raw gas, and take out the sample after about 5 minutes.

[0156] At 550℃, total flow rate 50mL·min -1 , and reduced in a mixed gas of H2:N2 with a volume ratio of 5:45 for 2 h to obtain a NiTiAl-2 catalyst with a layered structure.

[0157] In the NiTiAl-2 catalyst provided in this embodiment, based on the mass of the catalyst being 100%, the mass content of Ni is 50wt%, and the mass content of metal Ti is 10wt%.

[0158] (II) NiTiAl-2 catalyst for carbon dioxide hydrogenation

[0159] This method is the same as the method for catalytic hydrogenation of carbon dioxide provided in Example 1, but the difference is that the catalyst is NiTiAl-2 catalyst, and the rest is the same as Example 1.

[0160] The reaction product detection method is the same as that in Example 1, and the detection results are shown in Table 1.

[0161] Example 3

[0162] (I) Preparation of NiCeAl-3 catalyst

[0163] Add appropriate amount of aluminum sulfate 18hydrate, urea or ammonium bicarbonate or oxalic acid and sodium tartrate to deionized water and stir at room temperature for 1-3 hours. After all of them are dissolved, transfer them to the reactor and place them in a 150℃ constant temperature box for crystallization for 6 hours. After the crystallization is completed, perform solid-liquid separation, and place the solid in a 60℃ constant temperature box for drying for 6-12 hours to obtain aluminum oxide.

[0164] Nickel nitrate hydrate, cerium nitrate hydrate, aluminum oxide and urea are stirred thoroughly with deionized water as solvent to completely dissolve, and then placed in a hydrothermal kettle and placed in a 120°C constant temperature box for crystallization for 12 hours. The product of the hydrothermal reaction is centrifuged, the precipitate is washed with distilled water until it is neutral, and the solid is placed in a 60°C constant temperature box to dry for 3 to 24 hours to obtain a catalyst precursor.

[0165] The obtained catalyst precursor solid powder was further subjected to structural topological transformation and treated at 550°C for 4h.

[0166] Finally, at 550 °C, the total flow rate was 50 mL min -1 , and reduced in a mixed gas of H2:N2 ratio of 5:45 for 2 h to obtain NiCeAl-3 catalyst.

[0167] In the NiCeAl-3 catalyst provided in this embodiment, based on the mass of the catalyst being 100%, the mass content of Ni is 50wt%, and the mass content of metal Ce is 10wt%.

[0168] (II) NiCeAl-3 catalyst for carbon dioxide hydrogenation

[0169] This method is the same as the method for catalytic hydrogenation of carbon dioxide provided in Example 1, except that the catalyst used is NiCeAl-3 catalyst, and the rest is the same as Example 1.

[0170] The reaction product detection method is the same as that in Example 1, and the detection results are shown in Table 1.

[0171] Example 4

[0172] (I) Preparation of NiCeAl-4 catalyst

[0173] Nickel nitrate hydrate, cerium nitrate hydrate and aluminum nitrate hydrate were added at a molar ratio of divalent cations to (trivalent cations + tetravalent cations) of 1:1, and deionized water was used as a solvent. They were fully stirred to completely dissolve and prepare 100 mL of a mixed salt solution of about 0.5 mol / L.

[0174] Prepare 100mL of 0.2mol / L mixed alkaline solution of sodium hydroxide and sodium carbonate and stir thoroughly to dissolve them completely.

[0175] In another beaker, add 50 mL of distilled water, slowly drip the alkaline solution and salt solution into it, and continue to stir. Use a pH meter to control the pH of the suspension to 9.5 ± 0.5. After all the salt solutions have been added, move the suspension into a constant temperature water bath, control the crystallization temperature to 90 ° C, and continue to stir for 12 hours.

[0176] After the crystallization is completed, the solid-liquid separation is performed, and the solid is washed with deionized water until it is neutral. The solid is then placed in a 60° C. constant temperature oven and dried for 3 to 24 hours to obtain a catalyst precursor.

[0177] The obtained catalyst precursor solid powder was further subjected to a structural topological transformation treatment at 550° C. for 4 h to obtain a NiCeAl-MMO catalyst.

[0178] NiCeAl-MMO catalyst (~20 mg) was dispersed in ethanol, then injected onto nickel foam and oven-dried at 60 °C for 2 h.

[0179] Finally, at 550 °C, the total flow rate was 50 mL min -1 , and reduced in a mixed gas of H2:N2 at a ratio of 5:45 for 2 h to obtain NiCeAl-4 catalyst.

[0180] In the NiCeAl-4 catalyst provided in this embodiment, based on the mass of the catalyst being 100%, the mass content of Ni is 50wt%, and the mass content of metal Ce is 10wt%.

[0181] (II) NiCeAl-4 catalyst for carbon dioxide hydrogenation

[0182] This method is the same as the method for catalytic hydrogenation of carbon dioxide provided in Example 1, except that the catalyst used is NiCeAl-4 catalyst, and the rest is the same as Example 1.

[0183] The reaction product detection method is the same as that in Example 1, and the detection results are shown in Table 1.

[0184] Example 5

[0185] (I) Preparation of NiCeAl-5 catalyst

[0186] Nickel nitrate hydrate, cerium nitrate hydrate and aluminum nitrate hydrate were added at a molar ratio of divalent cations to (trivalent cations + tetravalent cations) of 1:1, and deionized water was used as a solvent. They were fully stirred to completely dissolve and prepare 100 mL of a mixed salt solution of about 0.5 mol / L.

[0187] Urea is prepared into a mixed solution with deionized water as solvent, and stirred thoroughly to dissolve it completely. The mixed salt solution, mixed solution and nickel foam are placed in a reactor, and then the reactor is placed in a constant temperature box, the crystallization temperature is 150°C, and it is stirred continuously for crystallization for 12 hours.

[0188] After the crystallization is completed, the solid-liquid separation is performed, and the solid is washed with deionized water until it is neutral. The solid is then placed in a 60° C. constant temperature oven and dried for 3 to 24 hours to obtain a catalyst precursor.

[0189] The obtained catalyst precursor solid powder was further subjected to a structural topological transformation treatment at 550° C. for 4 h.

[0190] Finally, at 550 °C, the total flow rate was 50 mL min -1, and reduced in a mixed gas of H2:N2 at a ratio of 5:45 for 2 h to obtain a Ni-based catalyst NiCeAl-5 catalyst with a layered structure.

[0191] In the NiCeAl-10 catalyst provided in this embodiment, based on the mass of the catalyst being 100%, the mass content of Ni is 50wt%, and the mass content of metal Ce is 10wt%.

[0192] (II) NiCeAl-5 catalyst for carbon dioxide hydrogenation

[0193] This method is the same as the method for catalytic hydrogenation of carbon dioxide provided in Example 1, except that the catalyst used is NiCeAl-5 catalyst, and the rest is the same as Example 1.

[0194] The reaction product detection method is the same as that in Example 1, and the detection results are shown in Table 1.

[0195] Example 6

[0196] (I) Preparation of NiCeAl-6 catalyst

[0197] Nickel nitrate hydrate, cerium nitrate hydrate and aluminum nitrate hydrate were added at a molar ratio of divalent cations to (trivalent cations + tetravalent cations) of 1:1, and deionized water was used as a solvent. They were fully stirred to completely dissolve and prepare 100 mL of a mixed salt solution of about 0.5 mol / L.

[0198] Prepare 100mL of 0.2mol / L mixed alkaline solution of sodium hydroxide and sodium carbonate and stir thoroughly to dissolve them completely.

[0199] In another beaker, add 50 mL of distilled water, slowly drip the alkaline solution and salt solution into it, and continue to stir. Use a pH meter to control the pH of the suspension to 9.5 ± 0.5. After all the salt solutions have been added, move the suspension into a constant temperature water bath, control the crystallization temperature to 90 ° C, and continue to stir for 12 hours.

[0200] After the crystallization is completed, the solid-liquid separation is performed, and the solid is washed with deionized water until it is neutral. The solid is then placed in a 60° C. constant temperature oven and dried for 3 to 24 hours to obtain a catalyst precursor.

[0201] The obtained catalyst precursor solid powder was further subjected to a structural topological transformation treatment at 550° C. for 4 h.

[0202] Finally, at 550 °C, the total flow rate was 50 mL min -1 , and reduced in a mixed gas of H2:N2 at a ratio of 5:45 for 2 h to obtain a Ni-based catalyst NiCeAl-6 catalyst with a layered structure.

[0203] In the NiCeAl-6 catalyst provided in this embodiment, based on the mass of the catalyst being 100%, the mass content of Ni is 50wt%, and the mass content of metal Ce is 5wt%.

[0204] (II) NiCeAl-6 catalyst for carbon dioxide hydrogenation

[0205] This method is the same as the method for catalytic hydrogenation of carbon dioxide provided in Example 1, except that the Ce content in the NiCeAl-6 catalyst used as the catalyst is different, and the rest is the same as Example 1.

[0206] The reaction product detection method is the same as that in Example 1, and the detection results are shown in Table 1.

[0207] Example 7

[0208] (I) Preparation of NiCeAl-7 catalyst

[0209] Nickel nitrate hydrate, cerium nitrate hydrate and aluminum nitrate hydrate were added at a molar ratio of divalent cations to (trivalent cations + tetravalent cations) of 1:1, and deionized water was used as a solvent. They were fully stirred to completely dissolve and prepare 100 mL of a mixed salt solution of about 0.5 mol / L.

[0210] Prepare 100mL of 0.2mol / L mixed alkaline solution of sodium hydroxide and sodium carbonate and stir thoroughly to dissolve them completely.

[0211] In another beaker, add 50 mL of distilled water, slowly drip the alkaline solution and salt solution into it, and continue to stir. Use a pH meter to control the pH of the suspension to 9.5 ± 0.5. After all the salt solutions have been added, move the suspension into a constant temperature water bath, control the crystallization temperature to 90 ° C, and continue to stir for 12 hours.

[0212] After the crystallization is completed, the solid-liquid separation is performed, and the solid is washed with deionized water until it is neutral. The solid is then placed in a 60° C. constant temperature oven and dried for 3 to 24 hours to obtain a catalyst precursor.

[0213] The obtained catalyst precursor solid powder was further subjected to a structural topological transformation treatment at 550° C. for 4 h.

[0214] Finally, at 550 °C, the total flow rate was 50 mL min -1 , and reduced in a mixed gas of H2:N2 at a ratio of 5:45 for 2 h to obtain a Ni-based catalyst NiCeAl-7 catalyst with a layered structure.

[0215] In the NiCeAl-7 catalyst provided in this embodiment, based on the mass of the catalyst being 100%, the mass content of Ni is 50wt%, and the mass content of metal Ce is 15wt%.

[0216] (II) NiCeAl-7 catalyst for carbon dioxide hydrogenation

[0217] This method is the same as the method for catalytic hydrogenation of carbon dioxide provided in Example 1, except that the Ce content in the NiCeAl-7 catalyst used as the catalyst is different, and the rest is the same as Example 1.

[0218] The reaction product detection method is the same as that in Example 1, and the detection results are shown in Table 1.

[0219] Example 8

[0220] (I) Preparation of NiCeAl-8 catalyst

[0221] Nickel nitrate hydrate, cerium nitrate hydrate and aluminum nitrate hydrate were added at a molar ratio of divalent cations to (trivalent cations + tetravalent cations) of 1:1, and deionized water was used as a solvent. They were fully stirred to completely dissolve and prepare 100 mL of a mixed salt solution of about 0.5 mol / L.

[0222] Prepare 100mL of 0.2mol / L mixed alkaline solution of sodium hydroxide and sodium carbonate and stir thoroughly to dissolve them completely.

[0223] In another beaker, add 50 mL of distilled water, slowly drip the alkaline solution and salt solution into it, and continue to stir. Use a pH meter to control the pH of the suspension to 9.5 ± 0.5. After all the salt solutions have been added, move the suspension into a constant temperature water bath, control the crystallization temperature to 90 ° C, and continue to stir for 12 hours.

[0224] After the crystallization is completed, the solid-liquid separation is performed, and the solid is washed with deionized water until it is neutral. The solid is then placed in a 60° C. constant temperature oven and dried for 3 to 24 hours to obtain a catalyst precursor.

[0225] The obtained catalyst precursor solid powder was further subjected to a structural topological transformation treatment at 550° C. for 4 h.

[0226] Finally, at 550 °C, the total flow rate was 50 mL min -1 , and reduced in a mixed gas of H2:N2 at a ratio of 5:45 for 2 h to obtain a Ni-based catalyst NiCeAl-8 catalyst with a layered structure.

[0227] In the NiCeAl-8 catalyst provided in this embodiment, based on the mass of the catalyst being 100%, the mass content of Ni is 50wt%, and the mass content of metal Ce is 18wt%.

[0228] (II) NiCeAl-8 catalyst for carbon dioxide hydrogenation

[0229] This method is the same as the method for catalytic hydrogenation of carbon dioxide provided in Example 1, except that the Ce content in the NiCeAl-8 catalyst used as the catalyst is different, and the rest is the same as Example 1.

[0230] The reaction product detection method is the same as that in Example 1, and the detection results are shown in Table 1.

[0231] Comparative Example 1

[0232] (I) Preparation of NiAl-9 catalyst

[0233] 1) Nickel nitrate hydrate and aluminum nitrate hydrate are added at a molar ratio of divalent cations to trivalent cations of 1:1, and deionized water is used as a solvent. They are fully stirred to completely dissolve and prepare 100 mL of a mixed salt solution of about 0.5 mol / L.

[0234] Prepare 100mL of 0.2mol / L mixed alkaline solution of sodium hydroxide and sodium carbonate and stir thoroughly to dissolve them completely.

[0235] In another beaker, add 50 mL of distilled water, slowly drip the alkaline solution and salt solution into it, and continue to stir. Use a pH meter to control the pH of the suspension to 9.5 ± 0.5. After all the salt solutions have been added, move the suspension into a constant temperature water bath, control the crystallization temperature to 90 ° C, and continue to stir for 12 hours.

[0236] After the crystallization is completed, the solid-liquid separation is performed, and the solid is washed with deionized water until it is neutral, and then the solid is placed in a 60° C. constant temperature oven to dry for 3 to 24 hours to obtain a NiAl catalyst precursor.

[0237] The obtained catalyst precursor solid powder was further subjected to a structural topological transformation treatment at 550° C. for 4 h.

[0238] Finally, at 550 °C, the total flow rate was 50 mL min -1 , and reduced in a mixed gas of H2:N2 at a ratio of 5:45 for 2 h to obtain a Ni-based catalyst NiAl-10 catalyst with a layered structure.

[0239] In the NiAl-10 catalyst provided in this embodiment, based on the mass of the catalyst being 100%, the mass content of Ni is 50 wt%.

[0240] (II) NiAl-9 catalyst for carbon dioxide hydrogenation

[0241] This method is the same as the method for catalytic hydrogenation of carbon dioxide provided in Example 1, except that the catalyst is the NiAl-9 catalyst provided in this comparative example, and the rest is the same as in Example 1.

[0242] The reaction product detection method is the same as that in Example 1, and the detection results are shown in Table 1.

[0243] Example 9

[0244] (I) Preparation of NiZrAl-1 catalyst

[0245] Nickel nitrate hydrate, zirconium nitrate hydrate and aluminum nitrate hydrate are added at a molar ratio of divalent cations to (trivalent cations + tetravalent ions) of 1:1, and deionized water is used as a solvent. They are fully stirred to completely dissolve and prepare 100 mL of a mixed salt solution of about 0.5 mol / L.

[0246] Prepare 100mL of 0.2mol / L mixed alkaline solution of sodium hydroxide and sodium carbonate and stir thoroughly to dissolve them completely.

[0247] In another beaker, add 50 mL of distilled water, slowly drip the alkaline solution and salt solution into it, and continue to stir. Use a pH meter to control the pH of the suspension to 9.5 ± 0.5. After all the salt solutions have been added, move the suspension into a constant temperature water bath, control the crystallization temperature to 90 ° C, and continue to stir for 12 hours.

[0248] After the crystallization is completed, the solid-liquid separation is performed, and the solid is washed with deionized water until it is neutral. The solid is then placed in a 60° C. constant temperature oven and dried for 3 to 24 hours to obtain a catalyst precursor.

[0249] The obtained catalyst precursor solid powder was further subjected to a structural topological transformation treatment at 550° C. for 4 h.

[0250] Finally, at 550 °C, the total flow rate was 50 mL min -1 , and reduced in a mixed gas of H2:N2 ratio of 5:45 for 2 h to obtain a Ni-based catalyst NiZrAl-1 catalyst with a layered structure.

[0251] In the NiZrAl-1 catalyst provided in this embodiment, based on the mass of the catalyst being 100%, the mass content of Ni is 50wt%, and the mass content of metal Zr is 8wt%.

[0252] (II) NiZrAl-1 catalyst for carbon dioxide hydrogenation

[0253] This method is the same as the method for catalytic hydrogenation of carbon dioxide provided in Example 1, except that the catalyst used is NiZrAl-1 catalyst, and the rest is the same as Example 1.

[0254] The reaction product detection method is the same as that in Example 1, and the detection results are shown in Table 1.

[0255] Example 10

[0256] (I) Preparation of NiZrAl-2 catalyst

[0257] Nickel nitrate hydrate, zirconium nitrate hydrate and aluminum nitrate hydrate are added at a molar ratio of divalent cations to (trivalent cations + tetravalent cations) of 1:1, and deionized water is used as a solvent. They are fully stirred to completely dissolve and prepare 100 mL of a mixed salt solution of about 0.5 mol / L.

[0258] Prepare 100mL of 0.2mol / L mixed alkaline solution of sodium hydroxide and sodium carbonate and stir thoroughly to dissolve them completely.

[0259] In another beaker, add 50 mL of distilled water, slowly drip the alkaline solution and salt solution into it, and continue to stir. Use a pH meter to control the pH of the suspension to 9.5 ± 0.5. After all the salt solutions have been added, move the suspension into a constant temperature water bath, control the crystallization temperature to 90 ° C, and continue to stir for 12 hours.

[0260] After the crystallization is completed, the solid-liquid separation is performed, and the solid is washed with deionized water until it is neutral. The solid is then placed in a 60° C. constant temperature oven and dried for 3 to 24 hours to obtain a catalyst precursor.

[0261] The obtained catalyst precursor solid powder was further subjected to a structural topological transformation treatment at 550° C. for 4 h.

[0262] Finally, at 550 °C, the total flow rate was 50 mL min -1 , and reduced in a mixed gas of H2:N2 at a ratio of 5:45 for 2 h to obtain a Ni-based catalyst NiZrAl-2 catalyst with a layered structure.

[0263] In the NiZrAl-2 catalyst provided in this embodiment, based on the mass of the catalyst being 100%, the mass content of Ni is 50wt%, and the mass content of metal Zr is 15wt%.

[0264] (II) NiZrAl-2 catalyst for carbon dioxide hydrogenation

[0265] This method is the same as the method for catalytic hydrogenation of carbon dioxide provided in Example 1, except that the NiZrAl-2 catalyst is used as the catalyst, and the rest is the same as Example 1.

[0266] The reaction product detection method is the same as that in Example 1, and the detection results are shown in Table 1.

[0267] Embodiment 11

[0268] (I) Preparation of NiZrAl-3 catalyst

[0269] Nickel nitrate hydrate, zirconium nitrate hydrate and aluminum nitrate hydrate are added at a molar ratio of divalent cations to (trivalent cations + tetravalent cations) of 1:1, and deionized water is used as a solvent. They are fully stirred to completely dissolve and prepare 100 mL of a mixed salt solution of about 0.5 mol / L.

[0270] Prepare 100mL of 0.2mol / L mixed alkaline solution of sodium hydroxide and sodium carbonate and stir thoroughly to dissolve them completely.

[0271] In another beaker, add 50 mL of distilled water, slowly drip the alkaline solution and salt solution into it, and continue to stir. Use a pH meter to control the pH of the suspension to 9.5 ± 0.5. After all the salt solutions have been added, move the suspension into a constant temperature water bath, control the crystallization temperature to 90 ° C, and continue to stir for 12 hours.

[0272] After the crystallization is completed, the solid-liquid separation is performed, and the solid is washed with deionized water until it is neutral. The solid is then placed in a 60° C. constant temperature oven and dried for 3 to 24 hours to obtain a catalyst precursor.

[0273] The obtained catalyst precursor solid powder was further subjected to a structural topological transformation treatment at 550° C. for 4 h.

[0274] Finally, at 550 °C, the total flow rate was 50 mL min -1 , and reduced in a mixed gas of H2:N2 at a ratio of 5:45 for 2 h to obtain a Ni-based catalyst NiZrAl-3 catalyst with a layered structure.

[0275] In the NiZrAl-3 catalyst provided in this embodiment, based on the mass of the catalyst being 100%, the mass content of Ni is 50wt%, and the mass content of metal Zr is 18wt%.

[0276] (II) NiZrAl-3 catalyst for carbon dioxide hydrogenation

[0277] This method is the same as the method for catalytic hydrogenation of carbon dioxide provided in Example 1, except that the catalyst used is NiZrAl-3 catalyst, and the rest is the same as Example 1.

[0278] The reaction product detection method is the same as that in Example 1.

[0279] The test results are shown in Table 1 and Table 2. Table 1 shows the reaction temperature (T 50 ) and methane selectivity, Table 2 WHSV (mass space velocity) = 30000 mL / (g cat h), conversion and selectivity at a reaction temperature of 230°C.

[0280] Comparative Example 2

[0281] This comparative example provides a nickel-based catalyst prepared by an impregnation method using a metal oxide of ZrO2 / Al2O3 as a carrier, which is denoted as NiZrAl-S4. The specific preparation method of the catalyst is as follows:

[0282] The metal oxide powder of ZrO2 / Al2O3 was added to 50mL of nickel nitrate solution, maintaining the same acid-base properties and metal ion molar ratio as that of Example NiZrAl-2, followed by ultrasonication for 1h, standing overnight, and after crystallization, solid-liquid separation was performed, and the solid was washed with deionized water until neutral, and then placed in a 60°C thermostat for drying for 6-12h. The obtained solid powder was further treated under the same conditions as Example NiZrAl-2 to obtain the nickel-based catalyst NiZrAl-S4.

[0283] (II) NiZrAl-S4 catalyst for CO / CO2 hydrogenation to methane

[0284] This method is the same as the catalytic hydrogenation method provided in Example 1, except that the catalyst is the NiZrAl-S4 catalyst provided in this comparative example, and the rest is the same as in Example 1.

[0285] Table 1 CO2 hydrogenation to methane reaction results (WHSV = 30000mL / (g cat h))

[0286]

[0287]

[0288] Table 2 Results of CO2 hydrogenation to produce methane (WHSV = 30000 mL / (g cat h), reaction temperature is 230°C)

[0289] sample <![CDATA[CO2 conversion rate]]> Methane selectivity / % NiCeAl-1 77 ~100 NiTiAl-2 60 ~100 NiCeAl-3 72 ~100 NiCeAl-4 70 ~100 NiCeAl-5 66 ~100 NiCeAl-6 72 ~100 NiCeAl-7 69 ~100 NiCeAl-8 66 ~100 NiAl-9 20 ~100 NiZrAl-1 60 ~100 NiZrAl-2 70 ~100 NiZrAl-3 65 ~100

[0290] CO hydrogenation was carried out using NiAl-9, NiZrAl-1, NiZrAl-2 and NiZrAl-3 catalysts according to the method for catalytic carbon dioxide hydrogenation provided in Example 1, except that WHSV = 30000 mL / (g cat·h), H2 / CO=3:1, reaction temperature is 300℃, the results are shown in Table 3.

[0291] Table 3 CO hydrogenation to methane reaction results (WHSV = 30000 mL / g cat / h, H2 / CO=3:1, reaction temperature is 300℃)

[0292]

[0293]

[0294] NiAl-9, NiZrAl-1, NiZrAl-2 and NiZrAl-3 catalysts were used to carry out mixed hydrogenation of CO and CO2 according to the method for catalytic hydrogenation of carbon dioxide provided in Example 1, except that WHSV = 30000 mL / (g cat h), H2 / CO2 / CO=7:1:1, reaction temperature was 450°C. The results are shown in Table 4.

[0295] Table 4 Results of the reaction of CO and CO2 mixed hydrogenation to produce methane (WHSV = 30000 mL / (g cat ·h), H2 / CO2 / CO=7:1:1, reaction temperature is 450℃)

[0296] sample CO conversion <![CDATA[CO2 conversion rate]]> Methane selectivity / % NiAl-9 90 44 99 NiZrAl-1 92 56 99 NiZrAl-2 96 64 99 NiZrAl-3 94 58 99

[0297] Among them, CO / CO2 reaction rate = (the amount of CO / CO2 substance input into the system - the amount of CO / CO2 substance in the system after the reaction) / (time×catalyst mass).

[0298] CO / CO2 conversion rate = (the amount of CO / CO2 substance in the feed - the amount of CO / CO2 substance in the output) / (the amount of CO / CO2 substance in the feed).

[0299] Methane selectivity = methane production / (CO / CO2 consumption). "-100" in Table 1 and Table 2 indicates that the methane selectivity is higher than 99%, close to 100%.

[0300] By comparing the carbon dioxide reaction rate, conversion rate and methane selectivity in Tables 1 and 2, it is shown that different preparation methods have different performances on the carbon dioxide hydrogenation to methane reaction of the layered NiCeAl catalyst, among which the hydrogenation catalyst prepared by the pH method in Example 1 shows the best CO2 conversion rate. In addition, different Ce doping amounts have different effects on the reaction rate of CO / CO2 and the selectivity of methane on the NiCeAl catalyst, among which 10% Ce doping has the best performance and is better than the currently reported catalysts; different Zr doping amounts have different effects on the reaction rate of CO / CO2 and the selectivity of methane on the NiZrAl catalyst, among which the catalyst with a Zr content of 15wt% has the best performance. It can be seen that the design of the NiMAl catalyst can not only effectively regulate the element composition ratio, but also promote the CO2 adsorption activation ability by increasing the specific surface area and the number of basic sites, thereby obtaining a Ni-based catalyst with both high dispersion of the active component Ni and adjustable electronic properties of the metal-support interface structure, which has excellent performance and stability at a lower reaction temperature.

[0301] As shown in Tables 3 and 4, the catalyst of the present invention still maintains a high conversion rate and methane selectivity in the hydrogenation of CO to methane and the hydrogenation of a mixture of CO and CO2 to methane, indicating that the catalyst of the present invention and its preparation method can adapt to different feed gases and achieve higher reactant conversion rate and methane selectivity. In addition, different catalysts prepared by adjusting the element composition ratio and preparation method of the layered polymetallic hydroxide obtained different CO conversion rates and carbon dioxide conversion rates, which indicates that the catalytic hydrogenation reaction performance can be changed.

[0302] Figure 1 The XRD diagrams of NiAl and NiZrAl-LDHs show that the catalyst precursors NiAl and NiZrAl-LDHs have multiple characteristic diffraction peaks, which are basically consistent with the standard peaks of LDHs (Layered double hydroxides, LDHs, layered polymetallic hydroxides). This shows that these methods synthesized precursors with layered polymetallic hydroxide structures. At the same time, as the Zr doping amount increases, the intensity of the characteristic diffraction peak of LDHs weakens. This is because the ion radius of Zr is large, and it is distorted when entering the layer plate, and the crystallinity becomes weaker.

[0303] Figure 2 It is a catalyst of NiAl and NiZrAl, which is obtained after the structural topological transformation of NiAl and NiZrAl-LDH. The characteristic diffraction peaks of NiAl are mainly Ni and NiO, and the characteristic diffraction peaks of NiZrAl also have the diffraction peaks of ZrO2, which indicates that a supported Ni-based catalyst is obtained.

[0304] Figure 3The scanning electron microscope images of NiAl and NiZrAl-LDH show that their precursors are all layered structures. As the Zr content increases, the layers break, which is basically consistent with the XRD results.

[0305] In summary, the preparation method of the layered NiMAl catalyst uses nickel salt, metal M salt ((M salt is a divalent, trivalent, tetravalent, pentavalent metal ion salt) and aluminum salt as raw materials, an aqueous solution of a hydroxide-containing alkaline compound and a carbonate or urea or ammonium bicarbonate or oxalic acid as a precipitant, and is prepared by a pH method, an atomic layer deposition method, an alumina in-situ growth method, a foam metal loading method and a foam metal in-situ growth method to obtain a layered NiMAl catalyst. The preparation method of the present invention utilizes the adjustable layered metal elements to dope cerium to form a layered multi-metal hydroxide precursor, and the M element in the obtained catalyst is uniformly dispersed, and there is a strong interaction between the active metal Ni and the composite metal oxide carrier MAlO. The specific surface area of ​​the catalyst and the alkaline sites on the catalyst are changed by doping with different M, thereby affecting the catalytic activity. In addition, the NiMAl catalyst prepared by different methods has good dispersibility of the active metal Ni, and the metal-carrier interface promotes adjustable electronic properties. When it is used for CO / CO2 hydrogenation reaction, it has excellent performance and good stability at a lower reaction temperature.

[0306] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Application of a hydrogenation catalyst in CO / CO2 hydrogenation to methane, characterized in that: The hydrogenation catalyst is obtained by structural topological transformation and reduction of a catalyst precursor; The catalyst precursor has a layered multi-metal hydroxide structure, including a cation layer formed by metal cations and anions between the layers; the metal elements in the cation layer include Ni, M and Al, and M includes one or more of Ce, Zr, In, Mg, Fe, Co, Zn, La, Ce, Mn, Ca, Sr, Ba, Y and Cu; The temperature of the structural topological transformation is 200-1000° C., the time of the structural topological transformation is 0.1-48 hours, and the atmosphere of the structural topological transformation is one or more of vacuum, nitrogen, argon, helium, air and hydrogen.

2. The use according to claim 1, characterized in that: In the hydrogenation catalyst, the mass fraction of metal Ni is 0.1-70%, the mass fraction of metal M is 0.1-60%, and the mass fraction of metal Al is 0.1-60%.

3. The use according to claim 1, characterized in that: The reduction temperature is 200-800° C., the reduction pressure is 0.1-10 MPa, the reduction time is 1-12 hours, and the reduction atmosphere includes reducing gas or a mixed gas of reducing gas and protective gas.

4. A method for preparing a catalyst for producing methane, characterized in that: The methane production catalyst is the hydrogenation catalyst in claim 1, and the hydrogenation catalyst is obtained by structural topological transformation and reduction of a catalyst precursor; The catalyst precursor is prepared according to the pH method, comprising the following steps: A1) mixing a nickel source, an M source, an aluminum source and water to obtain a mixed salt solution; mixing a hydroxide-containing alkaline compound, a carbonate and water to obtain a mixed alkaline solution; A2) mixing the mixed salt solution and the mixed alkali solution, controlling the pH value to be 6-14, and performing crystallization to obtain a catalyst precursor.

5. A method for preparing a catalyst for producing methane, characterized in that: The methane production catalyst is the hydrogenation catalyst in claim 1, and the hydrogenation catalyst is obtained by structural topological transformation and reduction of a catalyst precursor; The catalyst precursor is prepared according to the in-situ growth method of alumina, comprising the following steps: B1) mixing aluminum sulfate 18hydrate, a precipitant, sodium tartrate and water to obtain a first mixed solution, and crystallizing the first mixed solution under a constant temperature condition to obtain aluminum oxide; B2) Mixing the nickel source, the M source, the aluminum oxide prepared in step B1), a precipitant and water to obtain a second mixed solution, and crystallizing the second mixed solution under a constant temperature condition to obtain a catalyst precursor.

6. A method for preparing a catalyst for producing methane, characterized in that: The methane production catalyst is the hydrogenation catalyst in claim 1, and the hydrogenation catalyst is obtained by structural topological transformation and reduction of a catalyst precursor; The catalyst precursor is prepared according to the foam metal in-situ growth method, which includes the following steps: C1) mixing a nickel source, an M source, an aluminum source and water to obtain a mixed salt solution; C2) mixing the mixed salt solution, the precipitant and the foamed metal, and crystallizing them under a constant temperature condition to obtain a catalyst precursor.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The nickel source includes one or more of nickel nitrate hydrate, nickel sulfate and nickel chloride; The aluminum source includes one or more of aluminum nitrate hydrate, aluminum chloride, aluminum sulfate and aluminum oxide; The M source includes one or more of M nitrate, M oxide, M sulfate, M chloride and M acetylacetonate; The hydroxide-containing alkaline compound includes sodium hydroxide and / or potassium hydroxide; The carbonate includes one or more of sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate; The precipitant includes one or more of urea, ammonium bicarbonate and oxalic acid.

8. The preparation method according to any one of claims 4 to 6, characterized in that: The molar ratio of the hydroxide-containing alkaline compound to the carbonate is (1-100):1; The molar ratio of the precipitant to the total metal ions is (1-28):

1.

9. A method for preparing a catalyst for producing methane, characterized in that: The methane production catalyst is the hydrogenation catalyst in claim 1, and the hydrogenation catalyst can also be prepared according to the foam metal loading method, and the specific steps are as follows: The catalyst precursor is subjected to structural topological transformation, and then the catalyst after structural topological transformation is dispersed in a solvent, injected into foamed metal, dried and then subjected to reduction treatment to obtain a hydrogenation catalyst.

10. A method for preparing a catalyst for producing methane, characterized in that: The methane production catalyst is the hydrogenation catalyst in claim 1, and the hydrogenation catalyst can also be prepared by atomic layer deposition, and the specific steps are as follows: The catalyst precursor is subjected to structural topological transformation, and then the catalyst after structural topological transformation is placed in an atomic layer deposition device, and a raw material gas containing M metal element and a diluent gas are introduced to perform atomic layer deposition to obtain a hydrogenation catalyst.

11. A catalyst for producing methane, prepared according to the preparation method according to any one of claims 4 to 10.

Citation Information

Patent Citations

  • Nickel-based catalyst, preparation method and application

    CN111589462A

  • Perovskite oxide modified supported Ni-based catalyst as well as preparation method and application thereof

    CN118079926A